YES Problem: a(s(x1)) -> s(a(x1)) b(a(b(s(x1)))) -> a(b(s(a(x1)))) b(a(b(b(x1)))) -> a(b(a(b(x1)))) a(b(a(a(x1)))) -> b(a(b(a(x1)))) Proof: String Reversal Processor: s(a(x1)) -> a(s(x1)) s(b(a(b(x1)))) -> a(s(b(a(x1)))) b(b(a(b(x1)))) -> b(a(b(a(x1)))) a(a(b(a(x1)))) -> a(b(a(b(x1)))) Matrix Interpretation Processor: dim=1 interpretation: [b](x0) = x0 + 1, [a](x0) = x0 + 1, [s](x0) = 8x0 orientation: s(a(x1)) = 8x1 + 8 >= 8x1 + 1 = a(s(x1)) s(b(a(b(x1)))) = 8x1 + 24 >= 8x1 + 17 = a(s(b(a(x1)))) b(b(a(b(x1)))) = x1 + 4 >= x1 + 4 = b(a(b(a(x1)))) a(a(b(a(x1)))) = x1 + 4 >= x1 + 4 = a(b(a(b(x1)))) problem: b(b(a(b(x1)))) -> b(a(b(a(x1)))) a(a(b(a(x1)))) -> a(b(a(b(x1)))) String Reversal Processor: b(a(b(b(x1)))) -> a(b(a(b(x1)))) a(b(a(a(x1)))) -> b(a(b(a(x1)))) Matrix Interpretation Processor: dim=4 interpretation: [1 0 0 1] [0] [1 0 0 0] [0] [b](x0) = [1 0 0 0]x0 + [1] [0 0 1 0] [0], [1 0 0 1] [0] [1 0 0 0] [1] [a](x0) = [1 0 0 0]x0 + [0] [0 1 0 0] [0] orientation: [3 0 1 2] [1] [3 0 1 2] [0] [2 0 1 1] [1] [2 0 1 1] [1] b(a(b(b(x1)))) = [2 0 1 1]x1 + [2] >= [2 0 1 1]x1 + [0] = a(b(a(b(x1)))) [1 0 1 1] [0] [1 0 1 1] [0] [3 1 0 2] [1] [3 1 0 2] [0] [2 1 0 1] [2] [2 1 0 1] [0] a(b(a(a(x1)))) = [2 1 0 1]x1 + [1] >= [2 1 0 1]x1 + [1] = b(a(b(a(x1)))) [1 1 0 1] [0] [1 1 0 1] [0] problem: Qed